APPROXIMATE BOUNDARY CONTROLLABILITY FOR THE SEMILINEAR HEAT EQUATION - Cabanillas Zannini, Víctor Rafael (2005)
We study the problem of the approximate boundary controllability associated to the semilinear heat equationThe work presents an adaptation for boundary control problems of a fixed point technique introduced by E. Zuazua in the context of the equation of the wave, which had also been applied in the study of the approximate controlability when the controls act inside the domain Ω.The demonstration that we present is constructive in the sense that we explicitly obtain a boundary control in function of the solution of the adjoint system associated to our problem.